Display of variability of bilateral features in taiga ticks in contrast conditions of habitation - A. Ya. Nikitin; A. S. Novitskaya; I. M. Morozov; D. E. Gavrikov; А. Я. Никитин; А. С. Новицкая; И. М. Морозов; Д. Е. Гавриков (Scientific Centre for Family Health and Human Reproduction Problems, 2015)
The current research is aimed at studying the changes in a ratio of symmetrical to asymmetrical forms based on the counting bilateral characters in Ixodes persulcatus samples in various living conditions. Phenotypic variation was described with the following indices: (of) for a dispersion of the number of bristles at the left and right side; (Sa) for actual and (St) for theoretical number of symmetrical specimens with the supposition of an independent manifestation of such characters at the both sides of a body; and the difference between Sa and St. 4 bilateral characters were studied on the coxae of the fourth leg of the ticks collected by dragging off the plants outside Irkutsk (299 specimens) and Bratsk (156 specimens). The both territories are characterized by an excess of Sa and St. The σd2 value was proved to be higher among the ticks outside Bratsk where they live in a difficult environment. Given that no differences were revealed in the average values of «Sa-St» index, being characteristic of a subdivision of samples, the observed difference in of values may be considered as a prove of an increased instability during ontogeny under adverse circumstances. Цель исследования - изучить характер изменения соотношения симметричных и асимметричных форм по 4 счетным билатеральным признакам четвертой коксы в выборках Ixodes persulcatus из пригородов Иркутска и Братска. Для обеих территорий установлено превышение доли симметричных форм над теоретически ожидаемым значением этого показателя не связанное с нарушением независимости проявления признаков с двух сторон тела. Показано, что особи из неблагоприятныхусловий жизни (окрестности г. Братска) имеют более высокий уровень нестабильности онтогенеза, что может влиять на их векторную активность.